Vibrio alginolyticus influences quorum sensing-controlled phenotypes of acute hepatopancreatic necrosis disease-causing Vibrio parahaemolyticus - Panida Paopradit (PeerJ, 2021)
Background Acute hepatopancreatic necrosis syndrome (AHPND) caused by Vibrio parahaemolyticus strain (VPAHPND) impacts the shrimp industry worldwide. With the increasing problem of antibiotic abuse, studies on quorum sensing (QS) system and anti-QS compounds bring potential breakthroughs for disease prevention and treatment. Methods In this study, the cell-free culture supernatant (CFCS) and its extract of V. alginolyticus BC25 were investigated for anti-QS activity against a reporter bacteria, Chromobacterium violaceum DMST46846. The effects of CFCS and/ or extract on motility, biofilm formation and extracellular polymeric substances (EPSs) of VPAHPND PSU5591 were evaluated. Moreover, the effects of V. alginolyticus BC25 on virulence of VPAHPND PSU5591 were investigated by shrimp challenge test. The potentially active anti-QS compounds presented in the extract and effect on gene expression of VPAHPND PSU5591 were identified. Results The CFCS of V. alginolyticus BC25 and its extract showed a significant anti-QS activity against the reporter bacteria as well as swimming and swarming motilities, biofilms, and EPSs production by VPAHPND PSU5591. Transcriptome analysis revealed that V. alginolyticus BC25 extract significantly reduced the flagella genes involved in biofilm formation and iron-controlled virulence regulatory gene of VPAHPND PSU5591. Whereas, the LuxR family transcriptional regulator gene, c-factor, a cell-cell signaling gene, and capsular polysaccharide were up-regulated. The potentially active anti-QS compounds identified in extract were Cyclo-(L-Leu-L-Pro), and Cyclo-(L-Phe-L-Pro). Furthermore, V. alginolyticus BC25 enhanced disease resistance against VPAHPND PSU5591 in tested shrimp larvae. Conclusion These findings suggest that V. alginolyticus BC25 could provide natural anti-QS and anti-biofilms compounds and has great ability to be used as biocontrol agent against VPAHPND infection in shrimp aquaculture.